2021
DOI: 10.3389/fbioe.2021.795830
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-17 Cytokines and Receptors: Potential Amplifiers of Tendon Inflammation

Abstract: Interleukin (IL)-17A, a pro-inflammatory cytokine that is linked to the pathology of several inflammatory diseases, has been shown to be upregulated in early human tendinopathy and to mediate inflammatory and tissue remodelling events. However, it remains unclear which cells in tendons can respond to IL-17A, and how IL-17A, and its family members IL-17F and IL-17AF, can affect intracellular signalling activation and mRNA expression in healthy and diseased tendon-derived fibroblasts. Using well-phenotyped human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…IL-17 has been shown to mediate the inflammatory response by stimulating the production of pro-inflammatory cytokines and tissue remodeling in human tenocytes. It is proposed as a potential therapeutic target in tendinopathy [42,43]. In our study, we found a negative correlation between IL-17A in the PRP and a functional improvement examined with the PRTEE questionnaire.…”
Section: Discussionsupporting
confidence: 60%
“…IL-17 has been shown to mediate the inflammatory response by stimulating the production of pro-inflammatory cytokines and tissue remodeling in human tenocytes. It is proposed as a potential therapeutic target in tendinopathy [42,43]. In our study, we found a negative correlation between IL-17A in the PRP and a functional improvement examined with the PRTEE questionnaire.…”
Section: Discussionsupporting
confidence: 60%
“…IL-17A is known to induce the expression of several proinflammatory cytokines. A canonical IL-17 target is IL-6, whose production is augmented when IL-17A acts synergistically with TNFα, which also leads to the production of IL-1β and IL-8 [ 81 , 94 , 95 , 96 , 97 , 98 ]. Additionally, IL-17A acts synergistically with IFNγ to increase the production of IL-8 and monocyte chemoattractant protein-1 (MCP-1) [ 96 , 97 ].…”
Section: Transcriptional Targets Of Il-17 Family Cytokinesmentioning
confidence: 99%
“…In addition, IL-17A induces the production of antimicrobial peptides (AMPs), such as β-defensin, and acute phase proteins, such as lipocalin [ 81 , 94 ]. Moreover, tissue remodeling matrix metalloproteinases (MMPs), which can lead to extracellular matrix destruction and tissue damage, are often induced by IL-17A signaling, notably including MMP1, MMP2, MMP3, MMP9, and MMP13 [ 98 , 100 , 104 , 105 , 106 , 107 ]. On the other hand, IL-17A downregulates tissue inhibitors of metalloproteinases (TIMP)1 and TIMP2 [ 106 ].…”
Section: Transcriptional Targets Of Il-17 Family Cytokinesmentioning
confidence: 99%
See 2 more Smart Citations